INTERFERENSI TUTURAN GURU PADA PROSES PEMBELAJARAN BAHASA INDONESIA DI SMP NEGERI 1 X KOTO KABUPATEN TANAH DATAR - Laila Fitri; Tessi Mulyani (BHASWARA: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
The learning process is a joint effort between teachers and students to share and process information. In the Indonesian language teaching, teachers can use several approaches. Among these are the communicative approach which emphasizes that the primary function of language is a tool for communicating. Contact the language is a language influence to other languages, either directly or indirectly, while bilingualisme means the use of two languages or more by a speaker. bilingualisme an early occurrence of interference. Interference is one of the linguistic events that occur as a result of language contact. Chosen speech teacher in the learning process as study materials, due to the speech teacher in the learning process there are still a lot of interference. Corresponding problems above, the purpose of this study was to describe the form of interference speech teacher at SMP Negeri 1 X Koto Tanah Datar in Indonesian language learning process. Type of research is qualitative research. Qualitative research is research that produces data that is descriptive, in the form of words in written or oral form. The method used in this research is descriptive method. Subjects in this study were three Indonesian teacher at SMP Negeri 1 X Koto. The method used in data collection is a method refer to. Data was collected by means of learning Indonesian recording is in progress. The data analysis technique used is descriptive analysis techniques. Results of the study revealed that there had been interference during the learning process, both interference at the level of phonological, morphological, syntactic, lexical, and semantic. This occurs because humans are basically mastered more than one language or bilingualisme influence and the tendency to use the first language into a second language by accident.